(3JYbjH Ydi GddeYI GdfhQGfjIs - (3eMeO Hf YHO GdbGOQ GdaGSis; (3HQgGf GdOjf YHO Gddg EHQGgje Hf MSf GdcQOi GdchQGfi GdTgQRhQi GdSgQGfi Ke GdeOfj,J (B1101 (3g` s ((3GdeOjfI s)
(3ChdgG (B:s
(3hQO YdjfG ef GdeOjfI GdeTQaI QSGdI ddTjN GdedG EHQGgje Hf MSf GdTgQRhQ SeGgG GddeYI GdSfjI ai JMbjb aCQOJ eQGLYJg ai Pdc ESJeOGOkG ef HMQ Ydheg s
(3BNQgG (B:s
(3aeG jMJed eecf GdJYde hJHjjfg hdfbJUQ Ydi gPG GdebOGQ ef GdcdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3Hg fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B35 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B21s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs